Hubungan antara penyakit jantung bawaan sianotik dan kejadian proteinuria - Sandro Kurnia; Muhammad Ali; Tina C L Tobing; Rizky Hardiansyah; Hafaz Zakky Abdillah (Fakultas Kedokteran USU, 2014)
Nephropathy is a known potential complication of cyanotic congenital heart disease. Chronic hypoxia occurs in cyanotic congenital heart disease that may affect renal function, either directly or through the secondary eritrositosis and increased blood viscosity. It was reported that the incidence of proteinuria occurred significantly in patients with cyanotic congenital heart disease. The mechanism of proteinuria in patients with cyanotic congenital heart disease is not fully known, but there are several possibilities. The first mechanism is due to blood hyperviscosity causing increased glomerular capillary pressure, which can lead to proteinuria. The second mechanism is due to increased glomerular capillary surface area causes disruption podosit function that can lead to proteinuria. Urine tests can be done to determine proteinuria in patients with cyanotic congenital heart disease to know the complications of the kidney.Keywords: cyanotic; congenital heart disease; proteinuria